Toleransi Antar Umat Beragama Perspektif Al-Quran - Desy Hendri Yanti; Exsan Adde; Muhammad Solihin; A Armadila (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The ability to hold oneself as an expression of this attitude of tolerance brings understanding and tolerance for differences of opinion. Dissent is normal and cannot be prohibited or suppressed. Only if all parties understand that this argument must be managed wisely in accordance with the noble values ​​of their religious beliefs, culture and traditions. The development and renewal of pluralistic theology in society is an important part of the world order which is shaped by ethnic, cultural and religious pluralism. Basically we are all brothers. Islam prohibits tolerance through the Qur'an and its hadiths. Indonesia is already known as a country that has a variety of diversity. The Qur'an's call for tolerance requires complexity and a willingness to accept all kinds of differences, including ethnicity, skin color, language, customs, culture, and religion. The Qur'an also states that the creation of the heavens and the earth, day and night, male and female is the decree of the Creator as a decree. Tolerance in Islam must always be maintained in accordance with Islamic law. Non-compliance with Sharia values ​​while maintaining tolerance has led to a shift in values ​​from tolerance that is justified within the boundaries of Islam to syncretization of religions with the principle of